Correction: Pereira et al. Migratory Ecology of Pseudoplatystoma fasciatum in the Amazon Basin Revealed by Otolith Microchemistry. Diversity 2024, 16, 378 - Luciana A. Pereira; Leandro Castello; Eric Hallerman; Donald Orth; Carolina Rodrigues da Costa Doria; Edson Rubens Ferreira Rodrigues; Fabrice Duponchelle (Diversity, 2025)
In the original published article [...]